2021
DOI: 10.1186/s12958-021-00705-4
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with melatonin improves ovarian tissue cryopreservation for transplantation

Abstract: Backgroud Melatonin has anti-inflammatory and antioxidative actions at the mitochondrial level. This indole-containing molecule may protect ovarian grafts during the process of cryopreservation. Therefore, we aimed to determine whether melatonin pretreatment improves rat ovarian graft quality. Methods Twenty-six female rats were allocated to two study groups of thirteen animals each: 1) control group: ovaries cryopreserved using the standard protoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Shiroma et al found that melatonin promoted faster resumption of the estrous cycle compared to control and increased the expression of mature follicles, collagen type I, von Willebrand factor, Ki-67, and cleaved caspase-3 on estrogen receptors in the corpus lutea and ovaries. It has also been stated that there was a decrease in apoptosis in follicles, corpus lutea and collagen type III with TUNEL 22 .…”
Section: Discussionmentioning
confidence: 95%
“…Shiroma et al found that melatonin promoted faster resumption of the estrous cycle compared to control and increased the expression of mature follicles, collagen type I, von Willebrand factor, Ki-67, and cleaved caspase-3 on estrogen receptors in the corpus lutea and ovaries. It has also been stated that there was a decrease in apoptosis in follicles, corpus lutea and collagen type III with TUNEL 22 .…”
Section: Discussionmentioning
confidence: 95%
“…ROS are potent oxidizing and reducing agents, which activate neutrophil and lipid peroxidation, leading to cell membrane damage 19 . In the study by Shiroma ME et al 20 , it has been shown that melatonin can support better quality ovarian grafts in inflammatory processes and oxidative stress and explained that the purpose of cell protection is to prevent mitochondrial apoptosis by reducing bcl2 expression in I/R injuries that damage cells and mitochondria 20 While caspase-3 total index was significantly higher in Group 2 compared with Group 1 (*p<0.001), this index was significantly decreased in the pretreatment groups (Group 3 and Group 4) compared with Group 2 (**p<0.001).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies revealed that melatonin reduces oxidative stress in ovarian follicles via its antioxidative action, thereby protecting oocytes and granulosa cells. 13,22,23 Several studies reported that melatonin protects granulosa cells and oocytes from ROS by reducing oxidative stress. 24,25 Tamura et al 12 showed that melatonin blocked the inhibitory effect of H 2 O 2 on oocyte maturation via reduction of ROS in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Clinical trials have shown that melatonin improves the outcomes of infertile patients who have undergone assisted reproductive technologies including in-vitro fertilization and embryo transfer. 13 Melatonin inhibits ovarian damage caused by radiotherapy and plays an anti-radiation role mainly by scavenging free radicals. 14 When melatonin interacts with -OH, it forms a transitional indolyl, which has low toxicity and can continue to react with -OH to produce 3-hydroxyl melatonin.…”
Section: Introductionmentioning
confidence: 99%